Workshop Pendidikan Kewirausahaan Sejak Dini di Roudlotuljannah-Bilingual (Untuk Membentuk Karakter Anak dan Menyiapkan Generasi Penerus Yang Siap Akan Tantangan Ekonomi) - Nugroho, Tatas Ridho; Ainiyah, Nur; Isnaini, Nurdiana Fitri (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Entrepreneurship education must start at an early age, starting from the introduction stage and then becoming an entrepreneur agent. This is implemented for children to become entrepreneurs mentally and in character. This community service activity (PKM) is carried out to shape the character of children and prepare the next generation to be ready for economic challenges through an early entrepreneurship education workshop in roudlotuljannah-bilingual. Through the learning process, educators implement by integrating entrepreneurship education in each subject. Learning activities outside the classroom such as "Market Day" will certainly make students fun because the purpose of this activity is to train students' entrepreneurial spirit. In addition to selling, students are also required to make books of the buying and selling process. By getting used to students doing buying and selling transactions at the same time as making books, each student will gain direct experience of being a young entrepreneur and it is hoped that it will shape the mindset of students to live as an entrepreneur.